An ancient herb aloevera in dentistry: A review - Indavara Eregowda Neena; Edagunji Ganesh; Parameshwarappa Poornima; Roopa Korishettar (Wolters Kluwer Medknow Publications, 2015)
The Egyptians called Aloe the "plant of immortality" because it can live and even bloom without soil. Aloe vera is well-known for its marvelous medicinal properties. These plants are one of the richest sources of health for human beings coming from nature. It has been grown as an ornamental plant widely. Products of the plant are used in the treatment of various ailments. A. vera is gaining popularity in dentistry as it is completely natural and there are no side effects being reported with its use. This paper gives an overview of the uses of this miracle plant and its uses in dentistry. A. vera has been used in dentistry for its wound-healing effects, gingivitis, plaque control, and curing oral mucosal lesions. A. vera may also reduce the pain and duration of oral ulcers while speeding healing. The dentists should use A. vera at a level high enough to maximize its therapeutic benefit.